Paley-Wiener-type theorem for polynomial ultradifferentiable functions - Sharyn, S.V. (Carpathian Mathematical Publications, 2015)
The image of the space of ultradifferentiable functions with compact supports under Fourier-Laplace transformation is described. An analogue of Paley-Wiener theorem for polynomial ultradifferentiable functions is proved.